Rehabilitation of abandoned housing projects in Peninsular Malaysia and Singapore: A comparative analysis - Md Dahlan, Nuarrual Hilal (2011)
Abandoned housing projects is one of the housing problems in Peninsular Malaysia.Even though there are laws and policies provided by the Malaysian government to govern the housing industry, the abandoned housing projects problem is still an un-resolve issue for the Malaysian government.The real victims are the purchasers themselves.There are no specific or common ways to face the problems because the issues faced by the stakeholders vary for each and every abandoned housing project.This paper will discuss law and practice in the rehabilitation of abandoned housing projects in Peninsular Malaysia and compare with the position in the Republic of Singapore.From the comparative approach, certain suggestions will be forwarded at the end of the paper to carry out rehabilitation in Peninsular Malaysia and Singapore.